Emerging Technologies for Low‐Cost, Rapid Vaccine Manufacture. Issue 1 (10th December 2018) - Kis, Zoltán; Shattock, Robin; Shah, Nilay; Kontoravdi, Cleo
Abstract : To stop the spread of future epidemics and meet infant vaccination demands in low‐ and middle‐income countries, flexible, rapid and low‐cost vaccine development and manufacturing technologies are required. Vaccine development platform technologies that can produce a wide range of vaccines are emerging, including: a) humanized, high‐yield yeast recombinant protein vaccines; b) insect cell‐baculovirus ADDomer vaccines; c) Generalized Modules for Membrane Antigens (GMMA) vaccines; d) RNA vaccines. Herein, existing and future platforms are assessed in terms of addressing challenges of scale, cost, and responsiveness. To assess the risk and feasibility of the four emerging platforms, the following six metrics are applied: 1) technology readiness; 2) technological complexity; 3) ease of scale‐up; 4) flexibility for the manufacturing of a wide range of vaccines; 5) thermostability of the vaccine product at tropical ambient temperatures; and 6) speed of response from threat identification to vaccine deployment. The assessment indicated that technologies in the order of increasing feasibility and decreasing risk are the yeast platform, ADDomer platform, followed by RNA and GMMA platforms. The comparative strengths and weaknesses of each technology are discussed in detail, illustrating the associated development and manufacturing needs and priorities. Abstract : Current vaccine manufacturing approaches are not suitable for producing a high number of vaccine doses rapidly, in response to an infectious outbreak. To address this need, emerging vaccine platform technologies are reviewed, assessed and compared, with particular focus on the following 4 platform technologies: a) humanized, high‐yield yeast recombinant protein vaccines; b) insect cell‐baculovirus ADDomer vaccines; c) Generalized Modules for Membrane Antigens (GMMA) vaccines; d) RNA vaccines. The strengths and weaknesses of each of these vaccine platform technologies are evaluated and compared based on six criteria, outlining the required needs and priorities to further develop these vaccine manufacturing platform technologies.